Synthesis and study effect of preparation method and characterization of mixed metal oxide catalyst for FAME production: a comparative study / Nur Syahida Izma Shafie and Nur Alwani Ali Bashah - Shafie, Nur Syahida Izma; Ali Bashah, Nur Alwani (2020)
Studies relating to fatty acid metyl ester(FAME) have gained much interest in recent year due to the demand for eco-friendly energy resouce to replace petroleum. The common process to produce FAME is transesterification of vegetables oil/fats in the presence of the catalyst either homogenous or heterogenous catalyst. Homogenous catalyst is widely acceptable for their fast reaction, however the impact from the aqueous quenching lead to high cost and application of heterogenous catalyst has given attention by most of the researchers. The heterogenous catalyt, mixed metal oxide has known as excellent catalytic activity because of the increasing basic or acid sites and directly give high yield. In this review, the preparation method such as coprecipitation, impregnation and sol-gel been compared on their effect to the FAME yield. It is discussed in detailed how the preparation method effect the catalytic activity of the catalyst. In the comparison, co-precipitation method is the most frequently used and give better performance of the catalyst. Furthermore, characteristic of mixed metal oxide such as crystalline structure, morphology, surface area and functional group were also reviewed using various characterization method like X-ray diffraction (XRD), scanning electron microscope (SEM), brunauer-emmett-teller (BET) and fourier transform infrared spectroscopy (FTIR) respectively. This characterization necessity also relating to the catalytic activity. Catalytic activity is a function of its specific surface area, surface area, base strength and base site concentration. For active transesterification process, the characteristic of catalyst is high specific surface area, strong base strength, and high concentration of base sites. In this review, the comparison between metal mixed oxide has being made to review the effect of method and characterization.